Young communist review. Mounthly publ. by the National Committee of the Young Communist League. . Review. Weekly publ. by the National Council of the Young Communist League
Since (1940) titled: Review. Weekly publ. by the National Council of the Young Communist League; Since (194!):no.18: Weekly review. National Council...